(untitled) (University Journal of Zoology, Rajshahi University, 2010)
Key words: Labeo rohita; parasite; prevalence; abundance; mean density; infestation. DOI: 10.3329/ujzru.v28i0.5290 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 65-68